De Novo Mutations in MLL Cause Wiedemann-Steiner Syndrome - Jones, Wendy D.; Dafou, Dimitra; McEntagart, Meriel; Woollard, Wesley J.; Elmslie, Frances V.; Holder-Espinasse, Muriel; Irving, Melita; Saggar, Anand K.; Smithson, Sarah; Trembath, Richard C.; Deshpande, Charu; Simpson, Michael A. (American journal of human genetics, 2012)
Excessive growth of terminal hair around the elbows (hypertrichosis cubiti) has been reported both in isolation and in association with a variable spectrum of associated phenotypic features. We identified a cohort of six individuals with hypertrichosis cubiti associated with short stature, intellectual disability, and a distinctive facial appearance, consistent with a diagnosis of Wiedemann-Steiner syndrome (WSS). Utilizing a whole-exome sequencing approach, we identified de novo mutations in MLL in five of the six individuals. MLL encodes a histone methyltransferase that regulates chromatin-mediated transcription through the catalysis of methylation of histone H3K4. Each of the five mutations is predicted to result in premature termination of the protein product. Furthermore, we demonstrate that transcripts arising from the mutant alleles are subject to nonsense-mediated decay. These findings define the genetic basis of WSS, provide additional evidence for the role of haploinsufficency of histone-modification enzymes in multiple-congenital-anomaly syndromes, and further illustrate the importance of the regulation of histone modification in development.